Leveraging continuing education and implementation science approaches to improve the care of patients with myeloproliferative neoplasms. Issue 28 (1st October 2022) - Kim, Joseph; Mesa, Ruben A.; Carter, Cody; Nguyen, Anthony Loc; Lau, Eric; Sheth, Parthiv; Dalal, Suhani; Behl, Rajesh; Gutman, Pablo; Gracie-King, Linda; Viens, Marc David; Ocana, Victor
Abstract : 334 Background: Myeloproliferative neoplasms (MPN) represent a heterogenous group of disorders associated with complicated symptom profiles and a propensity for disease transformation that may portend poor prognosis. Clinicians treating patients with MPN may improve treatment planning, disease monitoring, and care coordination by ensuring they check for driver mutations, assess and document symptoms, and evaluate prognostic factors. MPN is relatively uncommon, so clinicians may forget to apply these practices. Blending continuing education with implementation science approaches may help clinicians provide consistent, high-quality care for patients with MPN. This project was supported by an educational grant from Bristol Myers Squibb. Methods: Three hospital-based cancer centers participated in this 18-month longitudinal, multiphase CME/CE and QI initiative. Each hospital performed a baseline assessment by reviewing how their clinicians diagnosed and treated MPN. This process involved chart reviews (N = 38), focus group discussions, and online surveys. Clinicians also participated in two CE interventions and identified ways to implement practice changes that would lead to better care. Each hospital developed improvement projects that addressed one or more of the following: molecular diagnostics, symptom assessment and documentation, prognostic scoring, and treatment selection/planning. Clinicians assessed the feasibility of ideas such as reflex testing protocols, scheduled audit/feedback, patient registries, and clinical documentation shortcuts (eg, SmartText/Phrases).Results: As a result of the CE activities combined with the QI projects, the following competency-based educational outcomes were observed among clinicians: 40% increase (29.6% to 70%) regarding prognostic risk stratification; 41% increase (25.9% to 66.7%) in personalizing treatment plans based on disease-/patient-specific factors; and 24% increase (47.4% to 71.4%) in prioritizing goals of treatment. Based on patient chart data, the QI projects resulted in 15.8% increase (84.2% to 100%) in patients with MPN receiving molecular testing (eg, JAK2, CALR, and MPL genes); 66.7% increase (0% to 66.7%) in patients with MPN who have a documented symptom burden score based on a validated tool (eg, MPN-10); 24.1% increase (34.2% to 58.3%) in patients with MPN who have a documented prognostic score (eg, DIPSS); and 38.8% increase (22.7% to 61.5%) in eligible patients with MPN who are treated with JAK inhibitors. Conclusions: This project demonstrates how multiphase education and QI methods can help clinicians improve care for patients with MPN. Implementation strategies that triggered appropriate reminders and facilitated clinical documentation were considered most useful and sustainable for routine clinical practice.